Respuesta :
we have that
35 + 30s - 45t
case A)
7⋅(5+30s−45t)---> 35+210s-315t-----> is not equivalent
case B)
5(7+6s−9t)----> 35+30s-45t------> is equivalent to 35 + 30s - 45t
case C)
(−35−30s+45t)×(−1)----> 35+30s-45t---> is equivalent to 35 + 30s - 45t
case D)
10×(3.5+3s−4.5)----> 35+30s-45----> is not equivalent
case E)
( 35/2 - 15s + 45/2t) ⋅ (-2)--->-35+30s-45t---> is not equivalent
the answer is
B. 5(7+6s−9t)
C. (−35−30s+45t)×(−1)
35 + 30s - 45t
case A)
7⋅(5+30s−45t)---> 35+210s-315t-----> is not equivalent
case B)
5(7+6s−9t)----> 35+30s-45t------> is equivalent to 35 + 30s - 45t
case C)
(−35−30s+45t)×(−1)----> 35+30s-45t---> is equivalent to 35 + 30s - 45t
case D)
10×(3.5+3s−4.5)----> 35+30s-45----> is not equivalent
case E)
( 35/2 - 15s + 45/2t) ⋅ (-2)--->-35+30s-45t---> is not equivalent
the answer is
B. 5(7+6s−9t)
C. (−35−30s+45t)×(−1)